High-throughput synthesis of Mo-Nb-Ta-W high-entropy alloys via additive manufacturing. (February 2020) - Moorehead, Michael; Bertsch, Kaila; Niezgoda, Michael; Parkin, Calvin; Elbakhshwan, Mohamed; Sridharan, Kumar; Zhang, Chuan; Thoma, Dan; Couet, Adrien
Abstract: High-entropy alloys (HEAs) are a class of alloys that can exhibit promising properties including enhanced irradiation resistance, high-temperature strength, and corrosion resistance. However, they exist in a relatively unexplored region of quasi-limitless composition space. Thus, to enable the development of promising compositionally complex alloys, such as HEAs, high-throughput methods are needed. Such high-throughput capabilities are developed and presented in this work. In situ alloying through additive manufacturing was employed to produce arrays of different HEA compositions. Sample arrays were then characterized by scanning electron microscopy (SEM), energy-dispersive X-ray spectroscopy (EDS), and X-ray diffraction (XRD), all while remaining on the build plate. The top surface of each sample was compositionally homogeneous, as determined by EDS, and each sample exhibited a single-phase, disordered crystal structure, as determined by XRD. CALculation of PHAse Diagrams (CALPHAD) modeling was used to determine the equilibrium phases of each HEA composition at lower temperatures, the results of which were compared with XRD results. Implications of high-throughput synthesis techniques and the coupling of high-throughput characterization and modeling techniques are discussed in the context of alloy development. Graphical abstract: Unlabelled Image Highlights: A high-throughput bulk materials synthesis technique was developed. HEA sample arrays were produced via in situ alloying of elemental powders. HEA samples were homogeneous and single-phase disordered BCC. SEM, EDS, and XRD was performed while samples remained on build plate. CALPHAD modeling was used to map the Mo-Nb-Ta-W composition space.